Application of the D5 discipline from the G8D method in solving quality management problems for NOK parts - Joanna Cyganiuk; Piotr Kuryło; Ali Al-Zubiedy; Magdalena Mazur (Budownictwo o Zoptymalizowanym Potencjale Energetycznym)
The article discusses what is the G8D method, focusing on the fifth discipline of this method, D5, which involves the selection and verification of permanent corrective actions for root causes and escape points. The rationale for applying the G8D method and using the D5 discipline of this method was analyzed for the case of a NOK part, specifically a part with an undrilled hole. The algorithm that must be applied to correctly go through all the steps of the D5 discipline has been presented, in order to obtain verified corrective actions both for the point in the process where NOK parts are produced and for the control point where NOK was not detected. The practical application of this discipline for selected initial conditions (the transition through disciplines D0-D4), as well as the solution for the problem of producing defective products that protect the production system from further manufacturing of such parts has been presented. In construction literature, a similar approach is applied in the quality management of industrial prefabricates, where systematic defect analysis leads to the optimization of production processes. The applicability of the D5 discipline and the Poka Yoke method for securing the production station against the possibility of producing a NOK part was presented.